THE SIGNIFICANCE OF ISLAMIC VALUES AS THE PRINCIPLES OF LIFE IN A MODERN WORLD - Muhammad Qorib (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2016)
Currently we are dealing and living in the great currents of globalization. The process of change takes place so quickly. According to Paul Streeten in his book, “Globalisation: Threat and Opportunity (2001)”, besides convenience globalization also gives variety of social changes. Streeten said that globalization gives birth to threat on the one side and the opportunity on the other side.1 Sociologically, threat and opportunity of course will also be faced by every religion as an important element of society. Therefore, inevitably, the roles of religion need to be revitalized. People still expect that religion can face various problems arising as a consequence of the changes. Komaruddin Hidayat even states that religion as a figure personifying the "superman" who is able to make a miracle to find a way out on a variety of issues that arise in the community.2 This paper will see how religion promotes the basic values to face the modern life. This paper uses a hermeneutic approach to the Quran and hadith as the basic values